Differentiation of Mycobacterium chelonei from M. fortuitum by ciprofloxacin susceptibility. - Collins, C. H. (Cambridge University Press, 1985)
Seventy-five strains of Mycobacterium fortuitum were inhibited by 3.0 mg/l ciprofloxacin but 36 strains of M. chelonei were resistant. The results correlated well with those obtained by the nitratase test. The ciprofloxacin sensitivity test is a useful supplement to the tests used to identify these two species.